Pengembangan Instrumen Penilaian Materi Biologi Perikanan Menggunakan Quizizz - Muhammad Fuad; Aminuddin; Riskayanti (Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to develop an assessment instrument for Fisheries Biology learning using the Quizizz application to enhance interactive and efficient evaluation. The research follows Thiagarajan’s 4-D development model: Define, Design, Develop, and Disseminate. In the Define stage, the study analyzes the need for an assessment instrument, Fisheries Biology content, and student characteristics. The Design stage involves creating the initial Quizizz-based instrument with a focus on validity and readability. The Develop stage includes expert validation, revisions, and trials with students to assess practicality and effectiveness. The final Disseminate stage aims to expand its implementation. Results show that the developed instrument is highly valid and practical for educators and students. It serves as an innovative alternative for digital learning assessment, enhancing effectiveness and student engagement in Fisheries Biology education.